2012
DOI: 10.1089/jmf.2011.0314
|View full text |Cite
|
Sign up to set email alerts
|

Flaxseed Does Not Enhance the Estrogenic Effect of Low-Dose Estrogen Therapy on Markers of Uterine Health in Ovariectomized Rats

Abstract: Flaxseed (FS) is an oilseed rich in phytoestrogens and n-3 polyunsaturated fatty acids, compounds that may attenuate bone loss during aging. We previously demonstrated using the ovariectomized (OVX) rat model of postmenopausal osteoporosis that 10% dietary FS combined with low-dose estrogen therapy (LD) preserves vertebral bone mass and strength more so than either treatment alone. However, it was prudent to also consider the effect of this intervention on uterine tissue as LD, and possibly FS, may have estrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“… ✓ Activity; – No Activity; [1] Rose and Connolly ( 1989 ); [2] Liu et al ( 2004 ); [3] Brooks et al ( 2004 ); [4] Colli et al ( 2012 ); [5] Sacco et al ( 2012 ) …”
Section: Comparison Of Mechanistic Potencies To Clinical Endpointsmentioning
confidence: 99%
“… ✓ Activity; – No Activity; [1] Rose and Connolly ( 1989 ); [2] Liu et al ( 2004 ); [3] Brooks et al ( 2004 ); [4] Colli et al ( 2012 ); [5] Sacco et al ( 2012 ) …”
Section: Comparison Of Mechanistic Potencies To Clinical Endpointsmentioning
confidence: 99%
“…There are only two reports concerning flaxseed influence on female reproductive organs besides the ovary. Sacco et al 46 observed the histomorphological changes in uteri of rats fed with flaxseed, similar to the changes induced by oestrogen, indicating uterine activation and growth. In the experiments of Vlckova et al 36 , the dietary flaxseed increased the thickness of the endometrium and myometrium in mice uteri.…”
Section: Effects On Female Reproductive Processesmentioning
confidence: 81%
“…observed in this study may be due to the timing of OVX. Although the time points in our study are similar to those commonly used in OVX rat studies of PUFA interventions and long bone health [63,64,65], OVX at three months of age causes a premature switch to bone remodeling from normal growth [66]. Therefore, for future study of the alveolar bone, OVX after three months of age may be necessary to limit the disruption to normal trabecular growth and development that may still be occurring at the mandible.…”
Section: Discussionmentioning
confidence: 99%